(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract Inclusive education is an educational approach that aims to include all students, regardless of their physical, intellectual, social, emotional, linguistic, or other conditions. This thesis explores the importance of inclusive education in fostering diversity and equality in learning environments. It examines the benefits of inclusive education for both students with and without disabilities, the challenges faced in implementing inclusive education, and strategies to overcome these challenges.